Near infrared spectroscopy (NIRS) applications in medical: non-invasive and invasive leukemia screening - Ismail, R. (Penerbit UTM Press, 2016)
Near Infrared Spectroscopy (NIRS) has been applied as analytical tool in numerous field of study due to its ability in non-invasive application. NIRS with the ability in providing the information on biological molecules shows a high potential as a diagnosis tool in medical as diseased related to biochemistry changes of the cell and tissue. This paper reviewed the application of NIR spectroscopy in leukemia screening and in other medical application. General comparison between invasive and non-invasive NIR spectroscopy method is provided. The author also proposed a new non-invasive NIRS method in leukemia screening and compared it with the previous invasive NIRS method.